2021
DOI: 10.1093/mnras/stab1163
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanic acid (HNCO) in the hot molecular core G331.512-0.103: observations and chemical modelling

Abstract: Isocyanic acid (HNCO) is a simple molecule with a potential to form prebiotic and complex organic species. Using a spectral survey collected with the Atacama Pathfinder EXperiment (APEX), in this work we report the detection of 42 transitions of HNCO in the hot molecular core/outflow G331.512-0.103 (hereafter G331). The spectral lines were observed in the frequency interval ∼ 160–355 GHz. By means of Local Thermodynamic Equilibrium (LTE) analyses, applying the rotational diagram method, we studied the excitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Similar implications were found in observations and models of HNCO, another tracer associated with outflow dynamics and chemistry (e.g. Rodríguez-Fernández et al 2010;Velilla Prieto et al 2015;Canelo et al 2021).…”
Section: Comparison With Observational Studiessupporting
confidence: 82%
“…Similar implications were found in observations and models of HNCO, another tracer associated with outflow dynamics and chemistry (e.g. Rodríguez-Fernández et al 2010;Velilla Prieto et al 2015;Canelo et al 2021).…”
Section: Comparison With Observational Studiessupporting
confidence: 82%
“…The simplest one, isocyanate radical (NCO), has been observed relatively recently in the line survey of L483 (Marcelino et al 2018), while isocyanic acid (HNCO) belongs among the early molecules detected in the universe dating back to 1972 (Snyder & Buhl 1972;Buhl et al 1972). HNCO is a well established interstellar molecule observed in the direction of a variety of sources such as TMC-1 (Brown 1981), IRAS 16293-2422 (Bisschop et al 2008;Coutens et al 2016), L483 (Marcelino et al 2018), NGC 6334I ⋆ Tables A.2, A.3, A.5, and A.6 are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/ (Ligterink et al 2020), G31.41+0.31 (Colzi et al 2021), Serpens SMM1 (Ligterink et al 2021), and G331.512-0.103 (Canelo et al 2021). Its protonated form, H 2 NCO + , had been tentatively observed in Sgr B2 by Gupta et al (2013), but later on its presence in space has been confirmed by Marcelino et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The original intensity, obtained in a scale of antenna temperature corrected for atmospheric attenuation (T A ), was converted to the main-beam temperature (T mb ) scale using the main-beam efficiencies η mb = 0.80 for SEPIA180 1 , and η mb = 0.75 and 0.73 for APEX-1 and APEX-2, respectively 2 (e.g. Canelo et al 2021). The Half Power Beam Width (HPBW) values vary between ∼17-39 .…”
Section: Observationsmentioning
confidence: 99%
“…The model consists of two zero-dimensional steps (i.e., the physical properties of the source are uniform and static), comprising the dark-cloud and the hotcore phases of star formation. The 1 st step, representing an initial dark-cloud phase, was computed using the elemental abundances listed in Table 6, as was computed in previous works about the chemistry of HNCO in G331 (Canelo et al 2021). For the physical parameters, we adopted a gas temperature and density of 10 K and 1 × 10 4 cm −3 , respectively.…”
Section: Chemical Modelingmentioning
confidence: 99%
See 1 more Smart Citation